A metal-based inhibitor of NEDD8-activating enzyme. - Hai-Jing Zhong (Public Library of Science (PLoS), 2012)
A cyclometallated rhodium(III) complex [Rh(ppy)(2)(dppz)](+) (1) (where ppy=2-phenylpyridine and dppz=dipyrido[3,2-a:2',3'-c]phenazine dipyridophenazine) has been prepared and identified as an inhibitor of NEDD8-activating enzyme (NAE). The complex inhibited NAE activity in cell-free and cell-based assays, and suppressed the CRL-regulated substrate degradation and NF-κB activation in human cancer cells with potency comparable to known NAE inhibitor MLN4924. Molecular modeling analysis suggested that the overall binding mode of 1 within the binding pocket of the APPBP1/UBA3 heterodimer resembled that for MLN4924. Complex 1 is the first metal complex reported to suppress the NEDDylation pathway via inhibition of the NEDD8-activating enzyme.